2017
DOI: 10.3389/fpsyg.2017.00074
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Team Health Climate for Health-Related Outcomes of White-Collar Workers

Abstract: Occupational health researchers and practitioners have mainly focused on the individual and organizational levels, whereas the team level has been largely neglected. In this study, we define team health climate as employees’ shared perceptions of the extent to which their team is concerned, cares, and communicates about health issues. Based on climate, signaling, and social exchange theories, we examined a multilevel model of team health climate and its relationships with five well-established health-related o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 92 publications
8
38
0
1
Order By: Relevance
“…A similar picture emerges for team members' organizational commitment, which is predominantly hampered by their individual (rather than team) work pace (Clausen & Borg, ), and for their psychosomatic symptoms, which are essentially caused by experiences of individual time pressure and physical demands rather than by team understaffing (Busch, Deci, & Laackmann, ). The latter findings resonate with more recent research showing that team members' individual job demands trigger psychosomatic symptoms and presenteeism and decrease their subjective general health, mental health, and work ability (Schulz, Zacher, & Lippke, ). Evidence that effects are less likely to be identified across levels also appears when potential buffering resources are conceptualized at different levels.…”
Section: A Multilevel Framework Of Stressors and Demands In Teamssupporting
confidence: 83%
“…A similar picture emerges for team members' organizational commitment, which is predominantly hampered by their individual (rather than team) work pace (Clausen & Borg, ), and for their psychosomatic symptoms, which are essentially caused by experiences of individual time pressure and physical demands rather than by team understaffing (Busch, Deci, & Laackmann, ). The latter findings resonate with more recent research showing that team members' individual job demands trigger psychosomatic symptoms and presenteeism and decrease their subjective general health, mental health, and work ability (Schulz, Zacher, & Lippke, ). Evidence that effects are less likely to be identified across levels also appears when potential buffering resources are conceptualized at different levels.…”
Section: A Multilevel Framework Of Stressors and Demands In Teamssupporting
confidence: 83%
“…In this direction, in a study by McGonagle et al (2014) among healthcare workers, supervisor support and skill discretion were found to moderate the negative relationship between job demands and WA. Schulz et al (2017) have highlighted similar findings: team health climate emerged as particularly important for older employees’ WA because the social context may support those compensation strategies that older workers may employ when job demands exceed their physical or mental capabilities.…”
Section: Introductionmentioning
confidence: 69%
“…Presenteeism is commonly found in healthcare professionals; musculoskeletal pain may be responsible for decreased work performance, and may cause difficulty in making the movements necessary for the exercise of the function (30) . Changes in physical and mental health, reduced ability to work and occurrence of presenteeism are likely to occur due to the organizational context of the workplace and the relationships between teams (31) . Workers with greater sense of well-being are less absent from work, reduce presenteeism and show the intention to remain in their work stations (32) .…”
Section: Discussionmentioning
confidence: 99%